The McMurdo Dry Valleys Long Term Research Program: New understanding of the biogeochemistry of the Dry Valley Lakes - Lyons, WB; Welch, KA; Priscu, JC; Laybourn-Parry, J; Moorhead, D; McKnight, D; Doran, DM; Tranter, PT (2001)
The McMurdo Dry Valleys Longâ€Term Ecological Research (MCMâ€LTER) site represents the highestâ€latitude location of the 24 LTER sites supported by the U.S. National Science Foundation. Although the perennial iceâ€covered lakes in the dry valleys have been investigated since IGY, detailed, ecosystemâ€based studies have been conducted on these lakes since 1993 by LTER investigators. A review of recent findings on the biogeochemistry and foodâ€ chain dynamics of these lakes is summarized within. The lakes are much more complicated and more dynamic than previously thought. The importance of collecting longâ€term data is imperative if an understanding of how these sensitive systems respond to climate change is to be gained. Â© 2001 Taylor & Francis Group, LLC.